IMPACT OF CANINE ASSISTED THERAPY ON EMOTIONS AND MOTIVATION LEVEL IN CHILDREN WITH REDUCED MOBILITY IN PHYSICAL ACTIVITY CLASSES - Niewiadomska, Monika; Makris, Maria (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Canine assisted therapy is increasingly used in the treatment of children with various diseases. The participation of a dog in classes evokes positive emotions in children, which are often an important factor in the success of a therapy. Purpose: The aim of this study was to present the influence of emotions on the level of motivation toward physical activity in children with reduced mobility. Material: The study involved six 5-year-old children, i.e. 5 boys and one girl, who had refused to participate in physical activity classes. They reacted with anxiety, anger and did not want to exercise. Assessment of feelings and emotions of the children was based on observations and interviews with parents. Results: After introducing a dog to the physical activity classes, the children changed their attitude not only to training, but also to themselves and their classmates. There was an observed increase in their motivation for the exercises. Such a significant impact of a dog on child’s emotions can be very important in the therapeutic process and is reported and recognized by many specialists. Conclusions: Canine assisted therapy sessions could be promoted in the treatment of children with locomotor impairment, as well as with other disabilities such as autism, obesity, cerebral palsy, learning difficulties and depression.